2007
DOI: 10.2138/am.2007.2573
|View full text |Cite
|
Sign up to set email alerts
|

Comparative compressibility and structural behavior of spinel MgAl2O4 at high pressures: The independency on the degree of cation order

Abstract: The equation of state and the crystal structure evolution with pressure were determined for two single crystals of pure natural MgAl2O4 spinels with different degrees of order. The two samples studied were cut from a larger single crystal and one of them was experimentally disordered at high temperature. The two crystals, showing an inversion parameter x of 0.27 and 0.15 at ambient conditions, were loaded together in a diamond anvil cell and their unit-cell edge was measured up to about 7.5 GPa at 14 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
6
29
0
Order By: Relevance
“…Largely normal spinels such as MgAl 2 O 4 tend to become more inverse with increasing pressure, and it has been observed that this compound disorders more with temperature under high-pressure conditions. 35,36 However, at ambient temperature, high pressure alone has only a negligible effect on the cation distribution, 37 which is also one of the assumptions in the thermodynamic model employed in this work.…”
Section: Possibility Of Cation Ordering In Tungsten-bronze-type Oxidesmentioning
confidence: 99%
“…Largely normal spinels such as MgAl 2 O 4 tend to become more inverse with increasing pressure, and it has been observed that this compound disorders more with temperature under high-pressure conditions. 35,36 However, at ambient temperature, high pressure alone has only a negligible effect on the cation distribution, 37 which is also one of the assumptions in the thermodynamic model employed in this work.…”
Section: Possibility Of Cation Ordering In Tungsten-bronze-type Oxidesmentioning
confidence: 99%
“…To date, much effort has been devoted to the experimental and computational study of physical properties of spinel compounds as a function of pressure (Kiefer et al 1997;Nestola et al 2002;Levy et al 2003;Reichmann and Jacobsen 2006), temperature (Askarpour et al 1993;Andreozzi et al 2000;Suzuki et al 2000), and at high magnetic and electric fields (e.g., Hong and Yoo 2006;Ito et al 2011). Nevertheless, there are still many open issues regarding the dependencies of the physical properties of spinels as a function of composition and crystal-chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…There has been excellent agreement on the T effect on the Mg-Al disorder process of the MgAl2O4-Sp at ambient P: x increases as T increases [42,47,48,50,51,[53][54][55][56][57]. As to the P effect at ambient T, discrepancy presumably exists because the order-disorder reaction could not be readily activated and did not adequately approach its equilibrium during the course of a conventional high-P study [52,90,91]. Thanks to Méducin et al [45] who conducted an investigation under simultaneously high-P and high-T conditions (up to 3.2 GPa and 1318 °C), the P effect at relatively high T has been well established: x increases as P increases.…”
Section: Mg-al Order-disorder State Of Synthetic Mgal2o4-spmentioning
confidence: 99%